2005
DOI: 10.4314/eamj.v82i3.9270
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for vaginal candidiasis among women seeking primary care for genital infections in Dar es Salaam, Tanzania

Abstract: Objective: To determine the prevalence and risk factors for vaginal candidiasis (VC) among women seeking primary care for genital infections. Design: Cross-sectional study. Setting: Ilala Municipal Hospital in Dar es Salaam, Tanzania. Subjects: Four hundred and sixty four women presenting with complaints of genital infections. Results: Of the 464 women examined, 177 (38.1%) had abnormal vaginal discharge, 68(14.7%) had genital ulcers, 272 (58.6%) had genital pruritis, 18 (3.9%) had genital warts and 58 (12.5%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
(23 reference statements)
3
12
2
Order By: Relevance
“…Those for Candida oesophagitis were painful swallowing, a feeling of obstruction on swallowing, substernal chest pain and discrete ulceration of the oesophagus [ 23 ]. The symptom for vaginal candidiasis was a cuddle milk discharge [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Those for Candida oesophagitis were painful swallowing, a feeling of obstruction on swallowing, substernal chest pain and discrete ulceration of the oesophagus [ 23 ]. The symptom for vaginal candidiasis was a cuddle milk discharge [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Oral thrush, which is the commonest form of oral candidiasis in Tanzania, is known as "Utando wa mdomoni" in Swahili language. Symptoms for candida oesophagitis were painful swallowing a feeling of obstruction on swallowing, substernal chest pain and discrete ulceration of the oesophagus (Connolly et al, 1989) and those for vaginal candidiasis was a cuddle milk discharge (Namkinga et al, 2005) known as "Maziwa ya mgando" in Swahili language.…”
Section: Methodsmentioning
confidence: 99%
“…We found that women with no education were less likely to have candidiasis than those with some education. Namkinga et al 23 and Bradshaw et al 24 reported a similar association. It is possible that educated women are more aware of genital hygiene and are more likely to use soap and water or other chemical agents to keep their genitals clean thus disturbing their vaginal flora.…”
mentioning
confidence: 74%